Abatacept improves both the physical and mental health of patients with rheumatoid arthritis who have inadequate response to methotrexate treatment. Issue 2 (19th September 2006) - Russell, A S; Wallenstein, G V; Li, T; Martin, M C; Maclean, R; Blaisdell, B; Gajria, K; Cole, J C; Becker, J-C; Emery, P
Abstract : Objective: To examine the impact of added abatacept treatment on health related quality of life (HRQoL) in patients with rheumatoid arthritis (RA) who have inadequate response to methotrexate (MTX). Methods: The impact of abatacept treatment on HRQoL was examined in a longitudinal, randomised double blind, placebo controlled clinical trial. Effects of treatment on HRQoL were examined using repeated measures analysis of covariance and comparing rates of change in HRQoL across treatment groups. The relationship between American College of Rheumatology (ACR) clinical markers and disease duration with changes in HRQoL indicators was also examined. Finally, a responder analysis was used to examine the percentage of patients who improved by 0.5 SD in 12 months or who reached the normative levels seen in the US general population. Results: Statistically significant improvements in the abatacept group relative to controls were observed across a range of HRQoL measures, including physical function, fatigue, all eight domains of the SF-36, and the physical and mental component summaries (PCS and MCS). Improvements were seen as early as day 29 for fatigue and for five out of eight SF-36 domains. By day 169, all HRQoL measures were significantly better with abatacept than with placebo. HRQoL gains were associated with greater ACR clinical improvement, and the effects were consistent for patients with different disease duration. A significantly greater percentage of patients treated with abatacept reached normative levels of PCS, MCS, physical functioning, and fatigue compared with patients treated with MTX alone. Conclusion: Combined abatacept and MTX treatment produces significant improvements across a wide range of HRQoL domains in patients with RA.